Reuse of A325 and A490 High-Strength Bolts - Bowman, Mark D.; Betancourt, Miguel (Engineering Journal, 1991)
The reuse of high-strength structural bolts often refers to the removal and subsequent reinstallation of bolts when a structural connection is reassembled. Although bolt reuse is not commonplace, it may be feasible for certain types of structures, such as temporary structures used in construction, reusable military structures, and rehabilitation projects of existing structures. Moreover, a moderate cost savings may be possible if the structural bolts are reused when the structure is reassembled. The primary purpose of this study was to provide information on the effect of reuse on the behavior of various high-strength structural bolts. The performance of bolts which either were loaded in direct tension or were continuously torqued to failure was also examined so that comparisons could be made with bolts that were repetitively tightened and loosened. The influence of lubrication applied to the threads was also studied.